Syncope. Cardiovascular collapse, cardiac arrest, and sudden cardiac death. Seizure in practice of family doctor - Mykhailovska, N. S.; Grytsay, A. V. (ZSMU, 2015)
The textbook compiled in accordance with the program of «General practice - family medicine». Guidelines are intended to help students prepare for practical classes and learn the material. Can be used for training of 6th-years students of international faculty, discipline «General practice - family medicine»